IMPLEMENTASI PELATIHAN STRATEGI PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MENGEMBANGKAN BAHASA ANAK USIA DINI - Lensiana Lensiana (UNIVERSITAS BENGKULU, 2017)
The purpose of this research is to improve teacher’s ability in improving language for AUD. This research use Penelitian Tindak Sekolah (PTS) method. Research results showing teacher learning practices observation average result at 1st cycle is 22,325 (58,125%), normal category, and 2nd cycle get average result is 3.325 (83,125%) good category. Observation result for language develop AUD 4-5 year old group, 1st meeting result 1,35 (33,75%) category children not yet grow up, 2nd result is 3,2 (80%) category children grow up at our hope. Observation language development in AUD 5-6 year old group result 1st meeting is 1.325 (33.125%) category children not yet grow up, in 2nd average result is 3,225 (80,625%) category children grow up at our hope.